An energy-efficient scalar control taking core losses into account. Issue 2 (5th March 2018) - Khoury, Gabriel; Ghosn, Ragi; Khatounian, Flavia; Fadel, Maurice; Tientcheu, Mathias
Abstract : Purpose: In the need to optimize the energy efficiency, control structures can have a positive effect by tracking the optimal operating point according to the speed and mechanical load of the motor. The purpose of this paper is to present an energy-efficient scalar control for squirrel-cage induction motors (IMs), taking into consideration the effect of core losses. Design/methodology/approach: The proposed technique is based on the modification of the stator flux reference, to track the best efficiency point. The optimal flux values are computed through an improved model of the IM including core losses, then stored in a look-up table. Findings: Simulations of the proposed scalar control are carried out, and results show the efficiency improvement when the flux is optimized especially at low load cases. Results were validated experimentally on two motors compliant with different efficiency standards. Practical implications: The proposed approach can be used in several fields and applications using the scalar-controlled IM with a proper implementation in variable speed drives, as in the cases of pumps, compressors and blowers. Originality/value: The proposed technique is compared to existing optimization methods in literature, and the results show an improvement in the dynamic performance and in the response delays. The approach is also compared to an optimization technique used in industries like Leroy-Somer for variable speed drives, and efficiency improvements are shown.